We are all equal: politics of very important people blue light security in South Africa - Maphumulo, Mashimane Njabulo; Masuku, Mfundo Mandla (Frontiers in Political Science, 2025)
South Africa is globally rated as the most unequal society, which does not conform to democratic principles. Inequality is perpetuated by uneven security provisions at the behest of the state, which entrenches elitism. The study investigates the extraordinary utilisation of Very Important People’s blue light security by politicians and the budgetary implications and multiplier effects, such as exacerbating inequalities in South Africa. In pursuit of the study’s noble course, Social Contract Theory is employed to explain how the government has broken the social contract with the electorate in pursuit of the protection of elite status while deserting service delivery. This paper utilises doctrinal legal research to interpret legislation governing the use of VIP blue lights and a comprehensive literature review as a complementary method due to the limited literature. The government is prioritising the security of politicians, while law enforcement continues to receive a decreasing budget amid persistent crime challenges. The conduct of VIP blue light security is found to be inconsistent with road regulations and exposes other road users to danger. The study recommended that the government reconsider the allocation of resources, centralise the procurement of VIP blue lights, and employ innovative strategies in areas with poor police visibility.